2011
DOI: 10.1111/j.1365-2699.2011.02589.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for multi‐scale spatial autocorrelation improves performance of invasive species distribution modelling (iSDM)

Abstract: Aim Analyses of species distributions are complicated by various origins of spatial autocorrelation (SAC) in biogeographical data. SAC may be particularly important for invasive species distribution models (iSDMs) because biological invasions are strongly influenced by dispersal and colonization processes that typically create highly structured distribution patterns. We examined the efficacy of using a multi-scale framework to account for different origins of SAC, and compared non-spatial models with models th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 85 publications
(111 reference statements)
1
55
0
1
Order By: Relevance
“…MAXENT (ver.3.3.3; http:// www.cs.princeton.edu/∼schapire/maxent/; accessed in August 2016) was used as a common ENM to model native and invasive niches of APIs in climatic space. This was done based on bioclimatic variables and occurrence localities using native (native model), invasive ranges (invasive model), and both native and invasive ranges (all model) (Warren et al, 2008;Václavík et al, 2012). All pixels were regarded as parts of the possible climate space of native and invasive ranges for the globally distributed APIs (Kolanowska, 2013).…”
Section: Climatic Niche Shift Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…MAXENT (ver.3.3.3; http:// www.cs.princeton.edu/∼schapire/maxent/; accessed in August 2016) was used as a common ENM to model native and invasive niches of APIs in climatic space. This was done based on bioclimatic variables and occurrence localities using native (native model), invasive ranges (invasive model), and both native and invasive ranges (all model) (Warren et al, 2008;Václavík et al, 2012). All pixels were regarded as parts of the possible climate space of native and invasive ranges for the globally distributed APIs (Kolanowska, 2013).…”
Section: Climatic Niche Shift Analysismentioning
confidence: 99%
“…All pixels were regarded as parts of the possible climate space of native and invasive ranges for the globally distributed APIs (Kolanowska, 2013). A logistic output format was used to visualize the identified potential niches of these APIs in the climate space of native and invasive ranges based on MAXENT modeling (Václavík et al, 2012). For climatic niche maps based on native and invasive ranges, each pixel had a value ranging from 0 to 1, with 0 representing the lowest climatic suitability of (not suitable at all) and representing 1 the highest climatic suitability (completely suitable) (Phillips et al, 2006;Warren et al, 2008).…”
Section: Climatic Niche Shift Analysismentioning
confidence: 99%
“…For example, Václavík et al (2012) used autocovariate logistic regression and spatial eigenvector modelling to incorporate spatial information into the model outputs in order to constrain projections of Sudden Oak Death in California, and found that these proxies for dispersal better predicted the presence of the pathogen compared to models calibrated only on abiotic factors. Invasive organism distributions are often driven by factors beyond environmental controls, and so a direct set of abiotic and biotic predictors may not plausible.…”
Section: Invasive Spreadmentioning
confidence: 99%
“…Many spatial approaches have been developed in order to overcome such limitations of non-spatial counterparts. These approaches include, but are not restricted to, regression kriging, simultaneous autoregressive modeling, conditional autoregressive modeling, spatial lag modeling, spatial error modeling, spatial eigenvector mapping, and geographically weighted regression [8,9,[17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%